The “Ricker Hills Tillite” (Victoria Land, Antarctica): new contribution for reconstructing the Cenozoic history of the East Antarctc Ice Sheet.) - BARONI, CARLO; SALVATORE, MARIA CRISTINA; FASANO F.; GIORGETTI G. (SGI, 2004)
A semi-lithified to lithified diamicton, the "Ricker Hills Tillite", outcrops in places under a discontinuous Late Pleistocene glacial drift on the homonymous nunatak in the Prince Albert Mts, to the South of David Glacier. The geomorphologic evolution of the area, the sedimentary facies, and the fabric of glacial deposits have been reconstructed through detailed geomorphologic and glacial-geologic surveys. The tillite has been described and sampled to investigate the dynamic of the glacier responsible of its deposition. Micromorphological description and petrographic analyses have been carried out on thin sections of impregnated samples. X-ray diffractometry and X-ray fluorescence spectrometry have been performed to determine the clay fraction mineralogical composition and the chemical composition of bulk rocks. The diamictite is generally massive, with a porphiric-related distribution, low sorting, low rounding and medium to high angularity. Chemical analyses indicate that samples derive from mixing of the Ferrar Group dolerites and the Beacon Supergroup sandstones. High smectite and kaolinite contents (from 47% to 78% and from 16% to 34%, respectively) characterize the clay minerals composition; illite and chlorite occur in minor amount. Deformation structures induced by glacial stress are visible in glacial deposits and in bedrock samples collected at the base of the tillite. Phyllosilicate reorientation patterns (plasmic fabrics) due to glacial stress are clearly visible. The morphological and compositional characteristics of this deposit indicate that an ice mass advanced on the Ricker Hills and deposited a glacial drift in climatic conditions warmer than present, with a diffused availability of water during deposition. Finally, the tillite experienced a continental weathering in wet condition with percolating water, as testified by illuviation features, by calcite infillings, and by the formation of clay minerals typical of temperate climates.